Praise the god of DX: A consideration of how to convince users to adopt transformation - Shiro Uesugi (International Telecommunications Society (ITS), 2024)
This essay examines the challenges hindering Digital Transformation (DX) in Japan, reflecting a nationwide lag in IT and DX adoption. Key barriers include legacy systems, a shortage of IT expertise, and cultural resistance. An anthropological perspective illuminates the cultural dimension of these challenges, revealing a deep-rooted attachment to tradition that impedes DX adoption. To overcome these cultural barriers, the essay proposes strategies emphasizing a gradual and respectful integration of digital solutions. Advocating for tailored strategies that acknowledge and facilitate the cultural shift is crucial for successful DX implementation in Japan.
Keywords: 330; Strategies for digital transformation; business models for digital transformation; behavioral change; anthropological aspects